Penyimpangan Etika Bisnis Usaha Mikro dalam Perspektif Fenomenologi Sechler dan Weber (Studi Kualitatif pada Produk Tahu dan Ayam Potong Oleh Usaha Mikro di Pasar Tradisional Harapanjaya, Kota Bekasi, Provinsi Jawa Barat, Indonesia) - Firdaus, Adhy (Universitas Brawijaya, Indonesia, 2013)
Despite of religious and moral values of Indonesian who should have strong influence in ethical value in their day-to-day life, some Indonesian micro scale entrepreneurs seems does not care about business ethics by using dangerous chemical substances such as fomalin to the 'tofu' and 'chicken meat' industries. The objective of this research is to uncover the phenomenon concerning of un-ethical business behavior on micro-scale businesses and its implications on management. The research was set in the traditional flea-market in the city of Bekasi, West Java area in Indonesia, by using qualitative research and Qualitative-fenomenologi design. The research is focused on why un-ethical business, the use of hazardous chemicals such as formalin, are hapenning on food sector of micro-scale entrepreneurs, specifically on Tofu, and Chicken's Meat Industries. We interviews many informants to obtain information to be analyzed. The research tools including notes, tape recording, photo, deep interviews, etc. The data were studied and processed with coding and theme analysis. Peer debriefing, triangulations, and auditing were used to maintain the credibility of research. After analyzing data, revisit the site, discussion with colleagues, the conclusions was made. The finding of this research are (1) Misunderstanding, misinformations, economic pressures, job pressures from supervisor/boss/markets made the mid-set of micro scale business do not feel guilty of their unethics business; (2) Business ethics of micro scale business influenced by environment, knowledges, economic pressures, and norms.